A brief review and clinical evidences of teriparatide therapy for atypical femoral fractures associated with long-term bisphosphonate treatment - Gao, Jianpeng; Liu, Xiao; Wu, Xiaoyong; Li, Xiaoya; Liu, Jianheng; Li, Ming (Frontiers in Surgery, 2023)
The risk of bisphosphonate (BP)-associated atypical femur fracture (AFF) has markedly increased over recent decades due to suppression of bone turnover, accumulation of structural micro-damage and reduction of bone remodeling consequent to long-term BP treatment. These medications further delay bone union and result in challenging clinical management. Teriparatide (TPTD), a synthetic human parathyroid hormone, exhibits unique anabolic effects and can increase bone remodeling and improve bone microarchitecture, furtherly promoting fracture healing and reducing the rate of bone non-union. In this study, we briefly define AFF as well as the effects of BPs on AFFs, detailed the role of TPTD in AFF management and the latest clinical therapeutic findings. We have confirmed that TPTD positively promotes the healing of AFF by reducing the time to bone union and likelihood of non-union. Thus, teriparatide therapy could be considered as an alternative treatment for AFF, however, further research is required for the establishment of effective clinical guidelines of TPTD use in the management of AFF.